DESCRIPTIVE MODEL OF SLIDING FRICTION PROCESSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Paper analyses the sliding friction coefficient of rubber on concrete, timber and ceramic tile surfaces depending on the weight of the sliding object and contact surface area. It has been established that increase in the weight of the object makes sliding friction coefficient to grow. In the case of increase in size of contact area, sliding friction coefficient between rubber and concrete also increases, but it decreases between rubber- timber and rubber- tile. The mathematical model for description of sliding friction process has been developed which can be used to determine optimal surface area and a pattern as well as optimal weight of the sliding object in order to provide sufficient sliding friction. Model has five independent constants. It includes the contact surface area, the weight and the velocity of the sliding object, sliding friction coefficient, temperature and time.